We have here to do the necessary operation with like terms in this expression. We can proceed as follows:
![-3+8y-6y-4=-3-4+8y-6y=-7+2y](https://img.qammunity.org/2023/formulas/mathematics/college/e7scp34va4bla995i96zqhlyedkjuq1gmu.png)
Therefore, we have that the result for this expression is 2y - 7.
We sum the like terms, in this case, 8y - 6y = 2y, and -3 - 4 = -7.
We need to be careful with the signs in the operations. We also need to remember that we write the sign of that number with the greatest absolute value.